Lecturas Feministas a la Crisis Global Contemporánea - Cayulef, María Gloria; Calquín, Claudia (Ariadna Ediciones, 2023)
This book emphasizes reflections on social relations and power that arepossible to delineate in the production/reproduction of inequality and precariousness in the ordercolonial, patriarchal and capitalist; in the radical or necropolitical violence that characterizes the scene contemporary, and along with it, the resistance processes that oppose and fracture it. From that will to oppose, fracture and also to transform, we emphasize the character committed to the investigations that each chapter presents, and that activist or militant seeks contribute to the construction of knowledge that transcends the traditional logic of thinking and produce knowledge. Thus, we distinguish the possibility of a research practice that contributes to the struggles and social transformations, either making them visible or generating theoretical debates in where political positions have a place.